Towards an Evaluation in an Indigenous context: The Case of a Mapuche School in Chile - Del Pino-Sepúlveda, Miguel; Cubillos, Froilán; Pinto, Diego (Revista Electrónica Educare, 2022)
Introduction. This study presents the case of a Mapuche school, which, based on the construction and recent validation of its Study Programs before the Ministry of Education of Chile, seeks the development of an educational evaluation in line with its study plans. The objectives were the following: 1. Identify the purpose of evaluation in an indigenous context based on the voices of its protagonists, and 2. Describe the conceptual elements that evaluation in an indigenous Mapuche context should have for its development. Method. It was participatory with the dialogic-kishu kimkelay ta che approach, together with Mapuche teachers, undergraduate students, school boys and girls, and scholars. The procedures of dialogic conversation and collective dialogue were used. The information collected was validated through a communicative analysis of the constructed knowledge. Results. The concept of kvmecegeam is highlighted as the purpose of the evaluation in terms of a formative assessment of learning, and the territorial and socio-cultural components as elements that allow directing and redirecting the evaluation process based on pertinent socio-historical and geographical characteristics. Discussion. An evaluation pertinent to the indigenous context is promoted, unlike the standardization imprint of learning and evaluation in Chile, where the cultural origin of each one is unknown. In this sense, guidelines or general orientations are offered to begin to develop a field of knowledge that is still little explored and not much progress has been made.